A Novel Loss-of-Function Variant in Transmembrane Protein 263 (TMEM263) of Autosomal Dwarfism in Chicken - Wu, Zhou; Derks, Martijn F. L.; Dibbits, Bert; Megens, Hendrik-Jan; Groenen, Martien A. M.; Crooijmans, Richard P. M. A. (Frontiers in Genetics, 2018)
Autosomal dwarfism (adw) in chickens is a growth deficiency caused by a recessive mutation. Characteristic for autosomal dwarfism is an approximately 30% growth reduction with short shank. The adw variant was first recognized in the Cornell K-strain of White Leghorns, but the genetic causal variant remained unknown. To identify the causal variant underlying the adw phenotype, fine mapping was conducted on chromosome 1, within 52 to 56 Mb. This region was known to harbor the causal variant from previous linkage studies. We compared whole-genome sequence data of this region from normal-sized and adw chickens in order to find the unique causal variant. We identified a novel nonsense mutation NP_001006244.1:p.(Trp59*), in the transmembrane protein 263 gene (TMEM263), completely associated with autosomal dwarfism. The nonsense mutation truncates the transmembrane protein within the membrane-spanning domain, expected to cause a dysfunctional protein. TMEM263 is reported to be associated with bone mineral deposition in humans, and the protein shows interaction with growth hormone 1 (GH1). Our study presents molecular genetic evidence for a novel loss-of-function variant, which likely alters body growth and development in autosomal dwarf chicken.